Japanese Rice Wine can reduce psychophysical stress-induced depression-like behaviors and Fos expression in the trigeminal subnucleus caudalis evoked by masseter muscle injury in the rats. Issue 1 (2nd January 2019) - Nakatani, Yosuke; Kakihara, Yoshito; Shimizu, Shiho; Kurose, Masayuki; Sato, Tsutomu; Kaneoke, Mitsuoki; Saeki, Makio; Takagi, Ritsuo; Yamamura, Kensuke; Okamoto, Keiichiro
ABSTRACT: We determined if Japanese Rice Wine (Sake) had inhibitory effects on stress-induced enhancement of masseter muscle (MM) nociception in the rats. Male rats were subjected to the repeated forced swim stress (FS) or sham conditionings from Day −3 to −1. Daily administration of Sake or saline was conducted after each stress conditioning. At Day 0 the number of Fos positive cells, a marker for neural activity, was quantified at the trigeminal subnucleus caudalis (Vc) region by MM injury with formalin. FS increased MM-evoked Fos expression in the Vc region, which was inhibited by Sake compared to saline administration. Sake did not alter the number of Fos positive cells under sham conditions, indicating that inhibitory roles of Sake on neural activity in the Vc region were seen under FS conditions. These findings indicated that Sake had inhibitory roles on stress-induced MM nociception at the Vc region in our experimental conditions. Graphical abstract: : Sake has inhibitory roles on psychophysical stress responses such as pain.